Controllability of 2-D systems: A survey - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a survey of recent results concerning controllability of 2-D systems is presented. Various types of linear and nonlinear 2-D systems with constant coefficients are discussed. Several controllability conditions for various kinds of 2-D systems are formulated without proofs. Moreover, many supplementary remarks and bibliographical comments are given. The relationships between different concepts of controllability are also explained.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka